Transpiration of woody plants in the desert Zone of mangistau - I.F. BELOZEROV,; A.A. IMANBAYEVA, (International Journal of Pharma and Bio Sciences, 2017)
The present research on the transpiration flow conducted in the arid conditions of Mangistau allowed three groups of introduced species to be distinguished: low transpiration (<250 mg/g per hour) - 3 types of trees; average transpiration (250-500 mg/g per hour) - 7 types of trees and shrubs; and high transpiration (>500 mg/g per hour) - 3 types of trees. Three types have been determined for the daily transpiration rhythm: "rising", "falling" and "variable". The intensity of the transpiration process, due to its considerable variability and multifactor nature, cannot be referred to the resistance criteria of woody plants, but at the same time, there is a noticeable connection between the biological stability of introduced species and the coefficient of transpiration variation. With the increase of its values, ​​the resistance of introduced species to the arid habitat conditions is generally enhanced due to their increased ability to the self-regulation of water exchange.